IFN-γ-Based ELISpot as a New Tool to Detect Human Infections with Borna Disease Virus 1 (BoDV-1): A Pilot Study - Lisa Eidenschink; Gertrud Knoll; Dennis Tappe; Robert Offner; Thomas Drasch; Yvonne Ehrl; Bernhard Banas; Miriam C Banas; Hans Helmut Niller; André Gessner; Josef Köstler; Benedikt M J Lampl; et al. (Viruses, 2023)
More than 40 human infections with the zoonotic Borna disease virus 1 (BoDV-1) have been reported to German health authorities from endemic regions in southern and eastern Germany. Diagnosis of a confirmed case is based on the detection of BoDV-1 RNA or BoDV-1 antigen. In parallel, serological assays such as ELISA, immunoblots, and indirect immunofluorescence are in use to detect the seroconversion of Borna virus-reactive IgG in serum or cerebrospinal fluid (CSF). As immunopathogenesis in BoDV-1 encephalitis appears to be driven by T cells, we addressed the question of whether an IFN-γ-based ELISpot may further corroborate the diagnosis. For three of seven BoDV-1-infected patients, peripheral blood mononuclear cells (PBMC) with sufficient quantity and viability were retrieved. For all three patients, counts in the range from 12 to 20 spot forming units (SFU) per 250,000 cells were detected upon the stimulation of PBMC with a peptide pool covering the nucleocapsid protein of BoDV-1. Additionally, individual patients had elevated SFU upon stimulation with a peptide pool covering X or phosphoprotein. Healthy blood donors (n = 30) and transplant recipients (n = 27) were used as a control and validation cohort, respectively. In this pilot study, the BoDV-1 ELISpot detected cellular immune responses in human patients with BoDV-1 infection. Its role as a helpful diagnostic tool needs further investigation in patients with BoDV-1 encephalitis.